2021
DOI: 10.1371/journal.pone.0255750
|View full text |Cite
|
Sign up to set email alerts
|

Anxious temperament and cyberchondria as mediated by fear of COVID-19 infection: A cross-sectional study

Abstract: This study’s main goal was to evaluate the association between anxious temperament and the fear of COVID-19-related self-infection and infection in loved ones (family members, friends, relatives) and cyberchondria. The sample consisted of 499 men and women aged between 18 and 72 who were gathered from the general population via an online recruitment platform. A numerical rating scale comprising 11 degrees of fear was used to assess participants’ COVID-19-related fear, and affective temperaments were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 46 publications
1
15
0
8
Order By: Relevance
“…Consistently with the previous literature on health anxiety ( McMullan et al, 2019 ), a more severe cyberchondria proved directly associated with a greater health anxiety. Moreover, cyberchondria also directly predicted the generalized anxiety dimension, adding strength to the few research exploring the link between cyberchondria and anxiety other than health anxiety ( Batıgün et al, 2020 ; Oniszczenko, 2021 ). In interpreting these findings, the partial overlap among the anxiety-spectrum constructs must be considered.…”
Section: Discussionmentioning
confidence: 80%
“…Consistently with the previous literature on health anxiety ( McMullan et al, 2019 ), a more severe cyberchondria proved directly associated with a greater health anxiety. Moreover, cyberchondria also directly predicted the generalized anxiety dimension, adding strength to the few research exploring the link between cyberchondria and anxiety other than health anxiety ( Batıgün et al, 2020 ; Oniszczenko, 2021 ). In interpreting these findings, the partial overlap among the anxiety-spectrum constructs must be considered.…”
Section: Discussionmentioning
confidence: 80%
“…The finding that the time spent over information about COVID-19 for more than 1 hour was associated with significant stress, anxiety, and depression is consistent with previous studies [17,18] as the excess time spent results in excess and/or repetitive exposure to misinformation and online health or COVID-19-related health search. Increased usage of online searches for medical information and the ensuing anxiety known as cyberchondria is considered as an independent risk factor for increased anxiety levels in the setting of COVID-19 [24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire was divided into three subscales: depression; anxiety; and stress. The total depression score was divided into normal (0-9), mild depression (10-13), moderate depression (14-20), severe depression (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The anxiety subscale score was divided into normal (0-7), mild anxiety (8-9), moderate anxiety (10)(11)(12)(13)(14), severe anxiety (15)(16)(17)(18)(19), and extremely severe anxiety .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laato, Islam, Islam, and Whelan ( 2020 ) identified that perceived severity and perceived susceptibility of COVID‐19 infection significantly contributed to cyberchondria after controlling for age and gender. In a 499 Polish community sample, Oniszczenko ( 2021 ) found that fear of COVID‐19 was associated with cyberchondria and it also mediated the relationship between anxious temperament and cyberchondria. Durmuş et al .…”
Section: Introductionmentioning
confidence: 99%